2015
DOI: 10.1016/j.yebeh.2014.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Differences in relatives' and patients' illness perceptions in functional neurological symptom disorders compared with neurological diseases

Abstract: ObjectiveThe illness perceptions of the relatives of patients with functional neurological symptom disorders (FNSD) have been little studied.We aimed to compare illness perceptions of relatives of patients with FNSD to those held by patients themselves. We used control pairs with neurological diseases (ND) to examine the specificity of the findings to FNSD. Material and methodsPatients with FNSD (functional limb weakness and psychogenic non-epileptic seizures) and patients with ND causing limb weakness and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This finding may also indicate that is helpful to include a carer in the consultation. A study of carer beliefs in dissociative seizures showed that they tended to have views which were likely to be more conducive to psychological treatment than the patient [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may also indicate that is helpful to include a carer in the consultation. A study of carer beliefs in dissociative seizures showed that they tended to have views which were likely to be more conducive to psychological treatment than the patient [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of non-attendance after referral to secondary specialist medical care from primary care suggest that young age (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), males, low socio-economic status, longer delay to appointment, transport and rapport are factors associated with missed appointments [15,16]. Reasons often given by patients for non-attendance include forgetting, apathy, illness, work commitments and clerical errors [17].…”
Section: Introductionmentioning
confidence: 99%
“…Patient and physician perspectives, collected through qualitative interviews and surveys, can inform new research directions, highlight conceptual struggles, and on-the-ground areas for improvement in clinician training, diagnosis, and treatment (4247). Education programs that involve direct contact with patients, outside of the clinic, have been shown to reduce stigma perceptions of “otherness” promoting deeper understanding and appreciation for these disorders (48).…”
Section: Approaches To Disrupt Boundaries Reduce Stigma and Advancementioning
confidence: 99%
“…In view of the fact that patients and relatives often have a different perspective on the seizures (Reuber et al, 2011, Whitehead et al, 2015a, Whitehead et al, 2015b), the views of both parties on how typical a particular attack was should be recorded. Another way of assessing typicality which has been proposed is to consider whether ‘all automatisms in induced seizures had been noted in at least some spontaneous seizures, and at least some automatisms in spontaneous seizures were noted in induced seizures’ (Walczak et al, 1994).…”
Section: Outpatient Synchronized Video-eegmentioning
confidence: 99%